2023
DOI: 10.1002/eem2.12466
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Atom Lithiophilic Sites Confined within Ordered Porous Carbon for Ultrastable Lithium Metal Anodes

Abstract: Attributing to the high specific capacity and low electrochemical reduction potential, lithium (Li) metal is regarded as the most promising anode for high‐energy Li batteries. However, the growth of lithium dendrites and huge volume change seriously limit the development of lithium metal batteries. To overcome these challenges, an ordered mesoporous N‐doped carbon with lithiophilic single atoms is proposed to induce uniform nucleation and deposition of Li metal. Benefiting from the synergistic effects of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…The FT-IR spectrum results of CCNM and SDBS-CCNMs are shown in Figure (d). The stretching vibration absorption peak strength of O–H in the hydroxyl group of SDBS-CCNMs is much stronger than that of CCNM at 3440 cm –1 , indicating that SDBS can increase the number of hydroxyl groups. The stretching vibration absorption peak of C–H in methylene represented at 2919 and 2843 cm –1 almost completely disappeared .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The FT-IR spectrum results of CCNM and SDBS-CCNMs are shown in Figure (d). The stretching vibration absorption peak strength of O–H in the hydroxyl group of SDBS-CCNMs is much stronger than that of CCNM at 3440 cm –1 , indicating that SDBS can increase the number of hydroxyl groups. The stretching vibration absorption peak of C–H in methylene represented at 2919 and 2843 cm –1 almost completely disappeared .…”
Section: Resultsmentioning
confidence: 95%
“…The stretching vibration absorption peak strength of O–H in the hydroxyl group of SDBS-CCNMs is much stronger than that of CCNM at 3440 cm –1 , indicating that SDBS can increase the number of hydroxyl groups. The stretching vibration absorption peak of C–H in methylene represented at 2919 and 2843 cm –1 almost completely disappeared . A new absorption peak near 1617 cm –1 observed on the SDBS-CCNMs spectrum was attributed to benzene ring skeleton vibrations ( v CC) .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have shown that encapsulating active Li metal into a host is efficacious in addressing the volume change issue [27][28][29] . Therefore, various micro/nanostructured hosts have been widely studied, including three-dimensional (3D) Cu current collectors [30,31] , reduced graphene oxide [32][33][34][35] , carbon fibers [36][37][38][39] , porous carbon granules [40][41][42][43] , and so on. Combined with the high lithiophilic sites, the plating/stripping behaviors and the cycling performances of the composite metallic Li anode have seen great improvement.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] Lithium (Li) metal anode (LMA) is widely regarded as the promising anode material for next‐generation high‐energy batteries owing to its extremely high theoretical specific capacity (3860 mAh g −1 ) and the lowest electrochemical reduction potential (‐3.04 V versus the standard hydrogen electrode). [ 4–6 ] Nonetheless, the practical applications of LMA are significantly impeded by several major obstructions such as unstable interface, undesired Li dendritic growth, and large volume change. [ 7,8 ] To be specific, the LMA with high activity can react with organic electrolyte to generate a rough and fragile solid electrolyte interphase (SEI) layer, which would destruct and reconstruct during cycling.…”
Section: Introductionmentioning
confidence: 99%